Constructive Criticism of the Role of Sharia Advocates in Legal Aid in the Contemporary Era - Budi Sastra Panjaitan (Faculty of Sharia, IAIN Metro, 2025)
This study examines the role of sharia advocates in providing legal aid in Indonesia during the contemporary era, driven by the increasing public demand for legal settlements based on Islamic values. This phenomenon shows the existence of a collective awareness of the importance of a legal approach that is not only legal-formal, but also ethical and spiritual. However, the complexity of modern law and structural challenges, such as the absence of specific regulations on Sharia advocates and limited professional training, are serious obstacles to carrying out the role ideally. In the midst of efforts to realize substantive justice, Sharia advocates are often trapped in a conventional legal framework (customs) that is not fully compatible with the Sharia values they carry. This research employs a descriptive qualitative method, combining a juridical-normative and sociological approach, through literature studies and interviews with relevant parties. The results of the study indicate that sharia advocates hold a strategic position in sharia-based dispute resolution, particularly amid the growing demand for legal settlements that reflect Islamic justice values. To carry out this role optimally, it is necessary to strengthen the capacity of personnel (lawyers), increase professional competence, provide adequate institutional support, and integrate Sharia values with Human Rights (HAM) principles in legal aid practice. Therefore, constructive criticism of the existing system is crucial to encourage reforms in aspects of education, regulation, and sharia advocacy practices that are more relevant, inclusive, and responsive to the dynamics of the law in the contemporary era.